Assessment of Local Factors Contributing to Occlusal Disturbances in the Replacement of Crown and Arch Defects with Fixed Dental Prostheses - Bida Олександр; Bida Олексій; Zabuga Юлія; Bida Віталій; Kravchenko Ярослав (Actual Dentistry, 2025)
Relevance. Based on the results of monitoring the dental health of the adult population, partial tooth loss, a complication of dental morbidity, remains at a high level, necessitating effective measures to replace it. The development of modern dentistry is aimed at increasing the involvement of digital methods in diagnostics, prosthetic planning, and the manufacture of orthodontic structures. According to the literature, the use of digital technologies enables the more accurate manufacture of dentures following the tissues of the prosthetic bed. Among the methods of comparative assessment of the quality of structures manufactured using different technologies, the degree of their functional adaptation is both the assessment of the marginal fit of restorations and the restoration of optimal occlusal relationships on orthopedic structures. Purpose: comparative analysis of the degree of restoration of occlusion parameters when replacing defects in the dentition with fixed dentures manufactured using analog and digital technologies, using the computerized T-Scan III system. Material and methods. Thirty-seven people aged 25 to 60 years with partial tooth loss of various sizes and topographies were examined, for whom metal-free denture structures were used for prosthetics. These individuals were divided into two clinical groups to obtain impressions using both analog and digital protocols. The group I consisted of 21 individuals, whose prosthetics were performed using metal-free denture structures. The clinical part involved obtaining analog working impressions with silicone impression materials. The group ІІ included 16 individuals, whose prosthetics were performed using metal-free dentures with the use of digital impressions. Digital impressions were performed using the SHINING 3D Aoralscan 3 intraoral scanner. The control group of the same age period consisted of 10 patients with intact dentition and physiological bite forms. Computerized analysis of occlusion indicators was performed using the T-Scan III system. The study studied the stereotype of functional loads according to the following quantitative and qualitative indicators: index of force asymmetry between the sides, time of occurrence of the maximum number of tooth contacts, time of disclusion, the presence of premature occlusal contacts on natural teeth and prosthetic structures and the presence of changes in the direction of the trajectory of the total occlusal load vector. Occlusion studies were conducted before prosthetics, during the fitting of the prosthetic structure in the oral cavity, and after occlusal correction and fixation in the oral cavity. Results. The results of the study of functional indicators of occlusion before prosthetics showed that the index of asymmetry of relative force between the sides of the dentition in patients in groups I and II with minor defects of the dentition increased significantly and led to a significantly non-physiological redistribution of loads, compared with the indicators obtained in patients with intact dentition due to the discrepancy of occlusal contacts and was 17.7 ± 3.8 and 18.9 ± 4.8%, respectively, against similar indicators of the control group — 4.7 ± 1.01% (p < 0.01). The obtained indicators differed not only from those of the control group, but also according to clinical pathology, including the number and degree of tooth crown destruction, the size and number of dental defects. Conclusions. Occlusiographic studies conducted in patients with varying degrees of tooth crown destruction and partial tooth loss showed an increase in the index of asymmetry of the relative force between the chewing sides, as well as the presence of premature contacts and incorrect location of the total occlusal load vector. The results of prosthetics using metal-free denture structures suggest that occlusion indicators are dependent on technological aspects. In particular, dental work made on patients of the first study group required additional fitting with occlusal correction. Clinical analysis of dental work made using digital technologies indicated a good marginal fit of the structures and optimal occlusal relationships that do not require correction.